2022
DOI: 10.1039/d2nr02337g
|View full text |Cite
|
Sign up to set email alerts
|

Dopant ion concentration-dependent upconversion luminescence of cubic SrF2:Yb3+,Er3+ nanocrystals prepared by a fluorolytic sol–gel method

Abstract: P-dependent relative spectral UCL distributions reveal different UCL quenching pathways in cubic phase SrF2:Yb3+,Er3+ and popular β-NaYF4:Yb3+,Er3+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Comparison with previously published studies of the up-conversion luminescence quantum yield of the SrF 2 :Yb:Er solid solutions in the form of both particles and single crystals 1,32,33,38 (Table 3) confirms the observed dependence of the up-conversion luminescence quantum yield on the particle size. The observed differences can be explained by different measurement techniques of the up-conversion luminescence quantum yield.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Comparison with previously published studies of the up-conversion luminescence quantum yield of the SrF 2 :Yb:Er solid solutions in the form of both particles and single crystals 1,32,33,38 (Table 3) confirms the observed dependence of the up-conversion luminescence quantum yield on the particle size. The observed differences can be explained by different measurement techniques of the up-conversion luminescence quantum yield.…”
Section: Resultssupporting
confidence: 87%
“…Monks et al 32 reported a quantum yield of 1.1% under an excitation intensity of 30 W cm À2 for the SrF 2 :Yb(13.5 mol%): Er(1.3 mol%) nanoparticles with an average size of about 15 nm. Kuznetsov et al 33 demonstrated the quantum yield of 2.8% in the SrF 2 :Yb(2.0 mol%):Er(2.0 mol%) powders with an average particle size of 120 nm at an excitation intensity of 10 W cm À2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methods are used for the synthesis of strontium fluoride powders [33,34], including precipitation from aqueous solutions [13-15, 35, 36], hydro-and solvothermal synthesis [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51], synthesis from solutions in a melt (flux technique) [52][53][54], sol-gel [55][56][57][58][59], combustion synthesis [60,61], synthesis using ionic liquids [52], thermal decomposition of precursors [62], high-energy ball milling [63], chemical reaction at the solution/vapor interface [64], etc. In the synthesis by precipitation from aqueous solutions by chemical reactions, various fluorinating agents were used -solutions of hydrofluoric acid [35], sodium fluoride [36,65], potassium fluoride [13-15, 36, 65], and ammonium fluoride [12,22,36].…”
Section: Introductionmentioning
confidence: 99%